Politik Identitas dalam Pilkada Surabaya 2020: Dampaknya terhadap Dinamika Politik, Stabilitas Sosial, dan Integrasi Nasional - Al Alimu Nur Rohman; Hamaz Zazirah Zamzam Fath; Dicky Febrian; Alifia Putri Siva (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the role of identity politics in the 2020 Surabaya mayoral election and its implications for political dynamics, social stability, and national integration. Using a qualitative case study approach, the research analyzes campaign strategies, media narratives, and public responses related to the utilization of religious and social identities during the election. The findings indicate that identity-based political strategies significantly influenced voter mobilization and electoral outcomes, contributing to the candidate’s victory. However, beyond electoral success, identity politics also generated social tensions, polarization, and public concern regarding the erosion of democratic substance. At the local level, identity politics strengthened political participation among certain groups, while simultaneously raising the risk of social fragmentation. At the national level, the Surabaya case reflects broader challenges to democratic consolidation and national integration in Indonesia’s plural society. The study concludes that while identity politics remains an unavoidable element of democratic competition, its excessive use may undermine social cohesion and democratic quality. Therefore, balanced political regulation, inclusive civic education, and ethical political practices are essential to sustaining a tolerant and integrative democratic system.